3 - Combating Illicit Financial Flows from Africa’s Extractive Industries and Implications for Good Governance: A Multi-country Study of Angola, the Democratic Republic of Congo and Nigeria - Igbatayo, S.A. (Africa Development, 2019)
Illicit Financial Flows (IFFs) from Africa have assumed crisis proportions in recent times. Global Financial Integrity (2010) estimates IFFs from Africa between 1970 and 2008 at more than US$ 1 trillion, an amount that dwarfs the combined inflows of developmental assistance and foreign direct investments into the continent over the same period. Nigeria leads other resource-rich African economies with the outflow, put at US$ 217.7 billion, or 30.5 per cent of the total. African Economic Outlook (2012) reveals that had the flight capital from Africa been invested efficiently, its outcome could have reduced the headcount poverty ratio for the continent by an additional 4 to 6 percentage points, thus halving extreme poverty by 2015 – a critical Millennium Development Goal (MDG) that eluded the region. Development experts have expressed concern that large-scale IFFs from Africa are draining the continent of critical resources necessary to drive development agenda. Africa’s extractive industries are particularly vulnerable to IFFs because of the complex and elaborate global value chains associated with the sector, which often transcend national borders. Among other things, elements of IFFs in the extractive sector include tax evasion, mis-invoicing, fraud and money laundering. The main objective of this article is to shed light on the threat posed by IFFs from Africa’s extractive sector and their implications for good governance. The article employs empirical data to analyse IFFs from Africa; adopting Angola, DRC and Nigeria in a multi-country study that reveals that huge financial resources have been lost to these countries over the past several decades, threatening the ability of African countries to achieve both the MDGs and the Sustainable Development Goals (SDGs) that succeeded them. Therefore, the article presents a policy framework underpinned by embracing the Extractive Industries Transparency Initiative; combating corruption; promoting institutional mechanisms; and deepening poverty reduction strategies.